Frizzled‐4 is required for normal bone acquisition despite compensation by Frizzled‐8. Issue 10 (27th January 2020) - Kushwaha, Priyanka; Kim, Soohyun; Foxa, Gabrielle E.; Michalski, Megan N.; Williams, Bart O.; Tomlinson, Ryan E.; Riddle, Ryan C.
Abstract: The activation of the Wnt/β‐catenin signaling pathway is critical for skeletal development but surprisingly little is known about the requirements for the specific frizzled (Fzd) receptors that recognize Wnt ligands. To define the contributions of individual Fzd proteins to osteoblast function, we profiled the expression of all 10 mammalian receptors during calvarial osteoblast differentiation. Expression of Fzd4 was highly upregulated during in vitro differentiation and therefore targeted for further study. Mice lacking Fzd4 in mature osteoblasts had normal cortical bone structure but reduced cortical tissue mineral density and also exhibited an impairment in the femoral trabecular bone acquisition that was secondary to a defect in the mineralization process. Consistent with this observation, matrix mineralization, markers of osteoblastic differentiation, and the ability of Wnt3a to stimulate the accumulation of β‐catenin were reduced in cultures of calvarial osteoblasts deficient for Fzd4. Interestingly, Fzd4‐deficient osteoblasts exhibited an increase in the expression of Fzd8 both in vitro and in vivo, which suggests that the two receptors may exhibit overlapping functions. Indeed, ablating a single Fzd8 allele in osteoblast‐specific Fzd4 mutants produced a more severe effect on bone acquisition. Taken together, our data indicate that Fzd4 is required for normal bone development and mineralization despite compensation from Fzd8. Abstract : Expression of Fzd4 is upregulated during the in vitro differentiation of osteoblasts. Mice lacking Fzd4 in mature osteoblasts exhibited an impairment in the femoral trabecular bone acquisition that was secondary to a defect in the mineralization process. Increases in Fzd8 expression in Fzd4 mutants suggested the possibility of overlapping functions.